He-Ne Laser Seed Treatment Improves the Nutraceutical Metabolic Pool of Sunflowers and Provides Better Tolerance Against Water Deficit - Mahmood, Saqib; Afzal, Beenish; Perveen, Shagufta; Wahid, Abdul; Azeem, Muhammad; Iqbal, Naeem (Frontiers in Plant Science, 2021)
Limited water availability is rendering continuous reduction of global agricultural area and crop production. It needs economic and ecofriendly solutions to meet the demand of increasing population. It was hypothesized that moderately drought tolerant crops with some additional eco-friendly and economic strategies may help to utilize limited water availability areas. A field study was conducted to grow a moderately drought tolerant crop (sunflower) with supportive seed treatment (He‐Ne lasers @ 300 mJ) for 0, 1, 2 and 3 minutes. Thirty days old plants were subjected to water limitation (100 and 50% irrigations). Harvesting was done at flowering (60 days old plant) and full maturity stage. Sunflower maintained growth and yield in water limitation with reduced achene number. At 50 % irrigation there was reduction in chlorophyll a, catalase activity, soluble sugars and anthocyanin with enhanced proline. He-Ne treatment with improved metabolizable energy, nutritional value and yield supported our hypothesis. Seeds with 2 minutes exposure of He-Ne laser performed best in terms of leaf area, leaf number, leaf biomass, % oil yield, 50 achenes weight, achene weight per plant, carotenoids and total soluble phenolics. Thereafter, best performing level of treatment (2 minutes) was subjected for HPLC-based phenolic profiling of leaves and GC-based fatty acid profiling of oil yield. Treatment accumulated nutraceutical phenolics and improved unsaturated to saturated fatty acids ratio of oil. In conclusion, He-Ne laser treated (2 minutes) sunflower seeds could be best strategy to utilized water limited areas for improved yield and nutritional value of sunflower.